Modeling of terracette‐hillslope soil moisture as a function of aspect, slope and vegetation in a semi‐arid environment. Issue 10 (19th February 2017) - Corrao, Mark V.; Link, Timothy E.; Heinse, Robert; Eitel, Jan U.H.
Abstract: In the semi‐arid western United States, water availability plays a defining role in land use. Soil moisture, vegetation, and microtopography are key variables in the hydrologic function of these ecosystems. Previous research has not addressed the influence of site‐specific aspect, vegetation, or slope gradient on terracette soil moisture patterns in semi‐arid rangelands. Therefore, the objectives of this study were to: (1) assess the influence of terracette site aspect, vegetation cover, and slope on soil moisture; (2) conceptualize conditions at the hillslope scale given terracette morphology; and (3) estimate the extent of terracettes at a regional scale. The Simultaneous Heat and Water (SHAW) model was used to simulate soil water dynamics of terracettes given variations in site conditions. These results were coupled with time‐of‐flight laser scans to quantify terracette bench and riser percent‐area, and statewide assessments of terracette extent using digital orthoimagery and a geographical information system (GIS). Modeling results indicated site aspect had minimal influence (±0.005 m 3 m −3 ) on terracette soil moisture. Vegetation, represented as leaf area index (LAI), had the single‐most influential effect on terracette volumetric water content ( θ v ) demonstrated by an inverse relationship of LAI to mean terracette hillslope θ v ; and slope increases of ≥15% on northern azimuths increased mean θ v which contrasted with southern azimuths for similar slope increases. Laser scanning results indicated bench width and riser length could be estimated from mean site slope ( R 2 = 0.82 risers and R 2 = 0.93 benches). Aerial orthoimagery/GIS assessments estimated >159 000 ha of terracettes throughout the State of Idaho, with >41 000 ha ( 26%) occurring on lands managed as grazing allotments. These findings provide an increased understanding of rangeland hydrologic processes as influenced by cattle density, vegetation, and terracettes which can aide land managers in their selection and application of best management practices on these lands. Copyright © 2017 John Wiley & Sons, Ltd.